1997
DOI: 10.1128/jcm.35.8.2061-2067.1997
|View full text |Cite
|
Sign up to set email alerts
|

Detection and clinical significance of extended-spectrum beta-lactamases in a tertiary-care medical center

Abstract: The prevalence of extended-spectrum ␤-lactamase (ESBL)-mediated resistance remains unknown for most hospitals, and national guidelines for testing and reporting ESBL-mediated resistance have not yet been developed. We undertook a study to determine the prevalence of ESBLs and the clinical need for testing in our tertiary-care medical center. Members of the family Enterobacteriaceae isolated over a 6-month period for which ceftazidime or ceftriaxone MICs were greater than 1 g/ml were tested for production of ES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
61
0
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(66 citation statements)
references
References 27 publications
(82 reference statements)
1
61
0
4
Order By: Relevance
“…No prospective studies were found regarding various treatment options and associated outcomes for serious infections due to ESBLproducing organisms. Limited data on treatment outcomes are available from seven case reports, [24][25][26][27][28][29][30] nine reports of nosocomial outbreaks [31][32][33][34][35][36][37][38][39] (which include brief descriptions of the subset of patients who required antimicrobial therapy), and two retrospective studies 40,41 (Table 1). Of note, most epidemiologic 40 Imp + Ak Ent, KP mostly Blood NS UNK 1 cured 1 34 Imp + Cp KP Blood, catheter-Imp ≤ 1.0 SHV-5 1 cured related Cp = NS 2 36 Imp + To KP Blood Imp = 0.12-1.0 UNK 2/2 cured To = 1-2 5…”
Section: Clinical Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…No prospective studies were found regarding various treatment options and associated outcomes for serious infections due to ESBLproducing organisms. Limited data on treatment outcomes are available from seven case reports, [24][25][26][27][28][29][30] nine reports of nosocomial outbreaks [31][32][33][34][35][36][37][38][39] (which include brief descriptions of the subset of patients who required antimicrobial therapy), and two retrospective studies 40,41 (Table 1). Of note, most epidemiologic 40 Imp + Ak Ent, KP mostly Blood NS UNK 1 cured 1 34 Imp + Cp KP Blood, catheter-Imp ≤ 1.0 SHV-5 1 cured related Cp = NS 2 36 Imp + To KP Blood Imp = 0.12-1.0 UNK 2/2 cured To = 1-2 5…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Imp KP Blood 4 cured, 1 died 17 35 25 CFT + Ak KP CSF, blood CFT ≤ 0.5-1.0 TEM-derived 1 cured 1 37 CFT Ent, mostly KP Septicemia CFT = 0.5-1.0 TEM-12, TEM-26 1 cured 1 27 CFT 2 g q6h KP Blood CFT = 0.75 (agar UNK 1 failed (cured with Cp disk diffusion) 400 mg q12h x 7 d) studies did not provide sufficient details on antibiotic regimen, dosage, and duration, or in vitro susceptibility of the agent. One retrospective study provided detailed information on antimicrobial therapy, particularly with extended-spectrum cephalosporins, 40 and 39 "Third-generation KP Urine NS TEM-10, TEM-26 2/2 cured cephalosporin" 4 32 CAX or CFT ± AG KP Urine CAX or CTX TEM-3-like, pI 6.3 4/4 cured = 0.5-4.0 (on selected isolates) 2…”
Section: Clinical Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, because such drugs were often found to be non-efficacious in vivo [12][13][14][15][16], it is broadly accepted today that, aside from those identified in urinary tract infections, ESBL-producing isolates should, by definition, be reported as resistant to all ESBL substrates [4]. This creates a real challenge for clinical microbiology laboratories, which should precisely detect the ESBL phenotype [6,[17][18][19][20][21][22][23][24]. Finally, the third important aspect of the presence of ESBLs results from their complex and dynamic evolution and epidemiology.…”
mentioning
confidence: 99%